(untitled) (Swiss Medical Weekly, 2014)
PRINCIPAL: Electroconvulsive therapy (ECT) is a treatment option for patients with bipolar disorder (BD). Alterations of markers have been reported following ECT. Aim: the aim of the present study was to assess the effect of adjunctive celecoxib on the serum cytokines of patient with BD who were undergoing ECT. METHODS: This study was a randomised, double-blind, placebo-controlled trial in 48 patients who were diagnosed with BD and ordered to undergo six or more ECT sessions. Patients were randomly assigned to receive either placebo or celecoxib (200 mg twice daily) starting a day before the first ECT and continuing throughout the end of the sixth ECT. Blood levels of interleukin-1β (IL-1β), interleukin-6 (IL-6), tumour necrosis factor-α (TNF-α) and high-sensitivity C-reactive protein (hsCRP) were measured before the first ECT and repeated after the first, the third and the sixth ECT sessions. Data were analysed by using SPSS version 13. RESULTS: Twenty-five patients (mean ± standard deviation age of 33.64 ± 9.97 years) were assigned to the celecoxib group and 23 patients (mean age of 32.61 ± 9.82 years) to the placebo group. This study found that the level of TNF-α was significantly lower (p = 0.04, t = 2.14, degrees of freedom 46) in patients receiving celecoxib compared with those on placebo at the last session of ECT. However, the other factors studied did not show any significant changes throughout the trial. CONCLUSIONS: Celecoxib was concluded to reduce TNF-α levels significantly in the patients at the end of the study. However, the differences in IL-1β, IL-6 and hsCRP between the two groups were not significant.